Redox zonation and oscillation in the hyporheic zone of the Ganges-Brahmaputra-Meghna Delta: Implications for the fate of groundwater arsenic during discharge. (December 2015) - Jung, Hun Bok; Zheng, Yan; Rahman, Mohammad W.; Rahman, Mohammad M.; Ahmed, Kazi M.
Abstract: Riverbank sediment cores and pore waters, shallow well waters, seepage waters and river waters were collected along the Meghna Riverbank in Gazaria Upazila, Bangladesh in Jan. 2006 and Oct.–Nov. 2007 to investigate hydrogeochemical processes controlling the fate of groundwater As during discharge. Redox transition zones from suboxic (0–2 m depth) to reducing (2–5 m depth) then suboxic conditions (5–7 m depth) exist at sites with sandy surficial deposits, as evidenced by depth profiles of pore water (n = 7) and sediment (n = 11; diffuse reflectance, Fe(III)/Fe ratios and Fe(III) concentrations). The sediment As enrichment zone (up to ∼700 mg kg −1 ) is associated with the suboxic zones mostly between 0 and 2 m depth and less frequently between 5 and 7 m depth. The As enriched zones consist of several 5–10 cm-thick dispersed layers and span a length of ∼5–15 m horizontally from the river shore. Depth profiles of riverbank pore water deployed along a 32 m transect perpendicular to the river shore show elevated levels of dissolved Fe (11.6 ± 11.7 mg L −1 ) and As (118 ± 91 μg L −1, mostly as arsenite) between 2 and 5 m depth, but lower concentrations between 0 and 2 m depth (0.13 ± 0.19 mg L −1 Fe, 1 ± 1 μg L −1 As) and between 5 and 6 m depth (1.14 ± 0.45 mg L −1 Fe, 28 ± 17 μg L −1 As). Because it would take more than a few hundred years of steady groundwater discharge (∼10 m yr −1 ) to accumulate hundreds of mg kg −1 of As in the riverbank sediment, it is concluded that groundwater As must have been naturally elevated prior to anthropogenic pumping of the aquifer since the 1970s. Not only does this lend unequivocal support to the argument that As occurrence in the Ganges-Brahmaputra-Meghna Delta groundwater is of geogenic origin, it also calls attention to the fate of this As enriched sediment as it may recycle As into the aquifer. Highlights: The hyporheic zone in the sandy Meghna riverbank displays a redox transition. Sediment As is enriched in two suboxic zones at depths of 0–2 m and 5–7 m. The As enriched sediment layers are only 5–10 cm thick but are 5–15 m long. Hundreds of years of groundwater As discharge is required for the As enrichment.